The economic aspect of a strategic partnership in Iran-Russia’s relations - Khavarinejad, Saeed (Иран и Россия в евроазиатском пространстве: диалог культур, государств, технологий : сборник материалов I Международной молодежной конференции (Томск, 2 мая 2023 г.))
Many observers are considering making Tehran-Moscow's relations into a strategic partnership as a result of Iran and Russia's growing closeness, while many others are opposed to this. The current study assesses the prospects for ties between Iran and Russia by looking at their economic interactions. After examining the areas where the two states cooperate, it is argued that due to structural problems in their mutual relations, particularly the low level of economic cooperation, their economic collaboration has not yet reached the expected level for a true strategic partnership.